DETEKSI DINI KANKER SERVIKS DENGAN TEKNIK INSPEKSI VISUAL ASAM ASETAT (IVA) DI DESA PANDUMAN - Linda Ika Puspita Ariati; Nurun Nikmah (STIKES NGUDIA HUSADA MADURA, 2021)
Early detection (screening) aims to detect precancerous changes, if there are changes and are not treated, can cause cancer. IVA is one of the simplest and cheapest cervical cancer screenings to do with high accuracy test results. The problems faced in the field are the lack of knowledge of WUS about early detection of cervical cancer with the IVA method and the low coverage of IVA services at the Jelbuk Public Health Center. This community service activity is to provide counseling about the importance of early cervical cancer screening and continued with IVA examination activities. The conclusion of this activity is that most of the participants' knowledge about cervical cancer and cervical cancer prevention increased and the IVA test results showed 97.3% (36 participants) were negative and 0.7% (1 participant) was suspected of having cervical cancer.